2017
DOI: 10.18632/oncotarget.23265
|View full text |Cite
|
Sign up to set email alerts
|

GRAM domain-containing protein 1B (GRAMD1B), a novel component of the JAK/STAT signaling pathway, functions in gastric carcinogenesis

Abstract: Dysregulated JAK/STAT signaling has been implicated in the molecular pathogenesis of gastric cancer. However, downstream effectors of STAT signaling that facilitate gastric carcinogenesis remain to be explored. We previously identified the Drosophila ortholog of human GRAMD1B in our genome-wide RNAi screen to identify novel components of the JAK/STAT signaling pathway in Drosophila. Here, we examined the involvement of GRAMD1B in JAK/STAT-associated gastric carcinogenesis. We found that GRAMD1B expression is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Furthermore, a genome-wide association study in chronic lymphocytic leukemia patients revealed that single nucleotide polymorphism in Gramd1b is associated with increased risk of disease in a European population 21 . In gastric cancer, GRAMD1B regulates cell survival by upregulating expression of the anti-apoptotic molecule Bcl-xL 22 . In this study, JAK/STAT signaling was found to positively regulate GRAMD1B expression in the breast cancer MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a genome-wide association study in chronic lymphocytic leukemia patients revealed that single nucleotide polymorphism in Gramd1b is associated with increased risk of disease in a European population 21 . In gastric cancer, GRAMD1B regulates cell survival by upregulating expression of the anti-apoptotic molecule Bcl-xL 22 . In this study, JAK/STAT signaling was found to positively regulate GRAMD1B expression in the breast cancer MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activation of JAK/STAT signaling is well‐established in cancers. Aberrant JAK/STAT signaling also is crucial to the development of GC, in particular, aberrant STAT3 expression has been implicated in GA patients 35–37 . Huang et al found that oxymatrine exhibits the effects via regulation of JAK/STAT signaling pathway and exhibits antitumor activity in GC 38 .…”
Section: Discussionmentioning
confidence: 99%
“…SOCS2 can be activated through tyrosine phosphorylation and may act as a downstream factor of the JAK/STAT pathway, providing a negative feedback regulation to this signaling pathway (38). Indeed, the JAK/STAT signal pathway is often dysregulated in gastric cancer (39). The JAK/STAT signaling pathway participates in multiple cancerous cellular processes: apoptosis, proliferation, metastasis and inflammation (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%